Total evidence phylogenetic analysis of Leiosauridae (Squamata) with focus on the 'para-anoles' and description of a new Urostrophus species from the Bolivian Andes. Issue 1 (31st December 2023) - Carvalho, André L. G.; Laspiur, Alejandro; Klaczko, Julia; Rivas, Luis Rolando; Rodrigues, Miguel Trefaut; Sena, Marco Aurélio de; Céspedes, Ricardo
Abstract : Only since the late 1980s have lizard specialists begun incorporating phylogenetic information to the classification of leiosaurids. These are among the most enigmatic South American lizards, with 35 currently recognised species arranged in six genera. To evaluate their relationships, we assembled a data set based on published and novel information containing 135 morphological characters and 11, 235 DNA base pairs (14 loci) for up to 52 terminals, including outgroups. We performed 13 analyses based on different optimality criteria (parsimony, maximum likelihood, and coalescent approach) and indel coding strategies (gaps coded as missing data or as a fifth state). We also evaluated the impact of phenotypic evidence on the phylogeny of leiosaurids, and investigated the level of informativeness and potential sources of topological conflict using a Quartet Sampling analysis. Phylogenetic analyses supported the monophyly of major leiosaurid clades, including subfamilies Enyaliinae and Leiosaurinae, and the 'para-anoles' clade ( Urostrophus + Anisolepis ). However, Urostrophus was inferred as paraphyletic, with U. vautieri forming a clade with Anisolepis . These relationships motivate the synonymization of Anisolepis Boulenger, 1885 with Urostrophus Duméril & Bibron, 1837. The monophyly of Pristidactylus and, surprisingly, of Enyalius, were also challenged, underscoring the need for additional phylogenetic work. Finally, we described Urostrophus chungarae sp. nov. from the Torotoro National Park, Potosí, Bolivia. This apparently rare leiosaurid was inferred as sister to U. gallardoi, a Chacoan species distributed in northern Argentina and southeastern Bolivia. We conclude with a revised classification of Leiosauridae and by pointing out a number of unresolved issues that require further systematic investigation. http://www.zoobank.org/urn:lsid:zoobank.org:pub:F60EB6CB-62B2-4EE3-B1A8-BEE3B2ED7A65